2019
DOI: 10.1038/s41598-018-38475-6
|View full text |Cite
|
Sign up to set email alerts
|

A galling insect activates plant reproductive programs during gall development

Abstract: Many insect species have acquired the ability to redirect plant development to form unique organs called galls, which provide these insects with unique, enhanced food and protection from enemies and the elements. Many galls resemble flowers or fruits, suggesting that elements of reproductive development may be involved. We tested this hypothesis using RNA sequencing to quantify the transcriptional responses of wild grapevine (Vitis riparia) leaves to a galling parasite, phylloxera (Daktulosphaira vitifoliae). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 98 publications
5
44
0
Order By: Relevance
“…In many galls the vasculature is generated to connect to the source of host plant tissue, and this process is suggested to be regulated by CLE and LRR–RLK genes, together with the other factors such as the auxin–dependent process shown above. A previous study with grapevine gall has shown that CLE44 and WOX4 are up–regulated in galls [13], supporting our hypothesis that these factors are commonly involved in vascular development in galls.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In many galls the vasculature is generated to connect to the source of host plant tissue, and this process is suggested to be regulated by CLE and LRR–RLK genes, together with the other factors such as the auxin–dependent process shown above. A previous study with grapevine gall has shown that CLE44 and WOX4 are up–regulated in galls [13], supporting our hypothesis that these factors are commonly involved in vascular development in galls.…”
Section: Resultssupporting
confidence: 89%
“…Shape and color of some galls show similarity to flowers and fruits. From the grapevine gall research, it is suggested that genes involved in reproductive organ development are up–regulated in developing galls [13]. Floral organ identity is determined by combined actions of the floral MADS genes [7475].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CK concentrations we report are much higher than those used by [62] (~9 pmol/g fwt), and how plants may respond to potentially much higher concentrations of CKs secreted by insects is as yet unknown. Several transcriptomic studies of gall systems report that gene expression in plant defense pathways are either unaffected or down-regulated in galls relative to un-galled plant tissues [19,[114][115][116][117][118][119][120], while other studies make no mention of effects of galling on host defenses or report up-regulation of plant defensive pathways [121][122][123][124][125]. Given the complicated relationships among phytohormones [126], there is likely to be crosstalk between the CK signaling pathway and other plant defense pathways, so perhaps CKs modulate defense.…”
Section: Role Of Cytokinins In Manipulating Nutrient Allocation and Hmentioning
confidence: 99%
“…In contrast to microbial systems, gall induction by animals is poorly understood for all but a tiny minority of economically important species, including root knot and cyst nematodes ( Heterodera , Globodera and Meloidogyne species) [1820], Hessian fly ( Mayetiola destructor ) [2124] and Phylloxera [25,26]. Nevertheless, with an estimated 30,000 species [27], gall inducing arthropods (and particularly insects) are abundant and ecologically important components of many biological communities [27].…”
Section: Introductionmentioning
confidence: 99%